Feasibility Study on Installation of Rooftop Photovoltaic System in Complied with Thailand Energy Building Code - Pathomthat Chiradeja; Atthapol Ngaopitakkul (My University, 2020)
Renewable energy especially solar energy has become a significant part in electrical power generation with its advantage in the environmentally friendly and current trend of decrease in installation cost. The photovoltaic (PV) system on a rooftop is one of the power generating system based on renewable energy that can fit building to utilize space efficiently. This paper is analyzing the feasibility of installing a solar PV rooftop on the building using a case study building located in Bangkok, Thailand. The performance will be evaluated in term of both energy and economic perspective. The comparison with Thailand building energy code also been done to show that overall energy consumption with PV system complies with the law. The result has shown that with rooftop photovoltaic system installation, annual energy consumption in the building can be reduced significantly and it can achieve feasibility in term of economic perspective.
Keywords: Installation; Photovoltaic mounting system; Photovoltaic Systems and Sustainability